A escrita numérica por crianças surdas bilíngües - Silva, Márcia Cristina Amaral da (2008)
This work intends to analyse how bilingual deaf children construct numerical writing; the factors and relations connected to it, as well as the hypothesis children have about this subject. The research is based on authors that deal with some aspects of numerical writing by hearing children. The information were collected through interviews with eleven deaf children from five to nine year olds in a special school for the deaf children. The method used in the interviews was the Piaget's critical-clinical. The results of this research show that deaf children have similar numerical writing hypothesis to those identified in hearing children. They also tell us that LIBRAS (Brazilians sign Language) is a fundamental factor in this construction so the school as a space where its use is continuous, can be considered as a very special place of promoting symbolic changes, necessary to these children's conceptual construction.